EFFECT OF ANTHROPOMETRIC CHARACTERISTICS AND MOTOR ABILITIES ON THE EXPLOSIVE FORCE AND COORDINATION IN STUDENT ATHLETES - Ibri Lulzim, (Sport Scientific And Practical Aspects, 2025)
With the aim of examining the influence of anthropometric characteristics and motor skills on the manifestation of specific motor skills of explosive strength and coordination, an experimental study was organized on a sample of 160 student athletes in Prizren. For the purposes of this research, 18 variables (8 anthropometric and 10 motor) were applied, which made up the predictor system of variables, and 4 specific motor ability tests that made up the criteria system of variables. The data were processed with descriptive and regression analyses. Based on the results of the research, it can be concluded that the anthropometric characteristics that were applied in the research did not have a significant impact on motor skills , coordination, while the applied predictor anthropometric variables showed that they had a significant impact on the criteria system of motor abilities of explosive power in student athletes, the results of the research also show that the predictor system of motor variables applied in the research has a significant impact on the criterion system of motor skills of coordination i explosive strength in student athletes.